1993
DOI: 10.1128/jb.175.21.7074-7080.1993
|View full text |Cite
|
Sign up to set email alerts
|

A cytoplasmic protein, NfrC, is required for bacteriophage N4 adsorption

Abstract: At least four genes are required for irreversible adsorption of bacteriophage N4. nfrA and nfrB have been characterized previously and encode an outer membrane protein and inner membrane protein, respectively. The nfrC gene product is characterized in detail in this study. We have mapped the nfrD locus to min 52 on the Escherichia coli linkage map. Maxicell analysis of nfrC and a null allele (nfrC2) cloned into a high-copy-number plasmid shows its gene product to be 42 kDa in size. We determined the nfrC nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 37 publications
1
40
0
Order By: Relevance
“…RffE is a UDP-N-acetylglucosamine-2-epimerase, and functions in the synthesis of UDP-N-acetylmannosamine, which is a component of the enterobacterial common antigen (Meier-Dieter et al, 1990). Whilst the precise mechanism is not understood, E. coli rffE (nfrC ) mutants are known to be resistant to infection with bacteriophage N4 (Kiino et al, 1993). To examine whether cps19fK is capable of complementing rffE mutations, we transformed the rffE mutant KI8828 (Kiino et al, 1993) with pJCP470 (which contains only the complete cps19fK ORF), or with pGEM-7Zf(þ).…”
Section: Insertion-duplication Mutagenesis Of Cps19f Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…RffE is a UDP-N-acetylglucosamine-2-epimerase, and functions in the synthesis of UDP-N-acetylmannosamine, which is a component of the enterobacterial common antigen (Meier-Dieter et al, 1990). Whilst the precise mechanism is not understood, E. coli rffE (nfrC ) mutants are known to be resistant to infection with bacteriophage N4 (Kiino et al, 1993). To examine whether cps19fK is capable of complementing rffE mutations, we transformed the rffE mutant KI8828 (Kiino et al, 1993) with pJCP470 (which contains only the complete cps19fK ORF), or with pGEM-7Zf(þ).…”
Section: Insertion-duplication Mutagenesis Of Cps19f Genesmentioning
confidence: 99%
“…Whilst the precise mechanism is not understood, E. coli rffE (nfrC ) mutants are known to be resistant to infection with bacteriophage N4 (Kiino et al, 1993). To examine whether cps19fK is capable of complementing rffE mutations, we transformed the rffE mutant KI8828 (Kiino et al, 1993) with pJCP470 (which contains only the complete cps19fK ORF), or with pGEM-7Zf(þ). The various strains, including the rffE wild-type parent E. coli MC4100 (Silhavy et al, 1984), were then examined for susceptibility to infection with N4 phage (Fig.…”
Section: Insertion-duplication Mutagenesis Of Cps19f Genesmentioning
confidence: 99%
“…Furthermore, a DxD motive (as described below) is not found in ATUXS2. Whereas the E. coli UDP-N-acetyl-Dglucosamine 2-epimerase (Kiino et al 1993; P27828) as expected do not adopt a typical type II membrane protein structure when run through the TMHMM version 2.0 server (Filter I), it is predicted to belong to the UDP-glycosyltransferase/glycogen phosphorylase superfamily by the SUPERFAMILY prediction server and is predicted to adopt a GT-B fold by mGen-THREADER. However, a DxD motif as described below is not found.…”
Section: Elimination Of False For Example Non-gt Hitsmentioning
confidence: 99%
“…Both host and phage proteins are thought to constitute the channels. To our knowledge, however, only N4 has been shown to require a specific cytoplasmic protein for the process of adsorption (10). Since N4 must translocate both its DNA genome and the virion RNA polymerase, the singular requirement for numerous gene products may be a reflection of the complexity of the N4 life cycle.…”
mentioning
confidence: 99%
“…The early events occurring during N4 infection require the injection of both its double-stranded DNA genome and a virion-encapsulated 320,000-Da RNA polymerase required for transcription of the early genes. A genetic analysis of N4 adsorption has identified four genes, nfrA to -D, required for this event (10,12). We have previously shown that the two tightly linked genes, ifl-A and nflB, encode an outer membrane protein with an apparent molecular size of 96 kDa and an inner membrane protein with an apparent molecular size of 69.5 kDa, respectively.…”
mentioning
confidence: 99%